Criminality and narrative in eighteenth-century England : beyond the law - Gladfelder, Hal (Johns Hopkins University Press, 2001)
"In Criminality and Narrative in Eighteenth-Century England, Hal Gladfelder shows how the trial report, providence book, criminal biography, and gallows speech came into new commercial prominence and brought into focus what was most disturbing, and most exciting, about contemporary experience. These narratives of violence, theft, disruptive sexuality, and rebellion compelled their readers to sort through fragmentary or contested evidence, anticipating the openness to discordant meanings and discrepant points of view which characterize the later fictions of Defoe and Fielding."--Jacket